Elevated CO2 Leads to Enhanced Photosynthesis but Decreased Growth in Early Life Stages of Reef Building Coralline Algae - Ordoñez, Alexandra; Wangpraseurt, Daniel; Lyndby, Niclas Heidelberg; Kühl, Michael; Diaz-Pulido, Guillermo (Frontiers in Marine Science, 2019)
Crustose coralline algae (CCA) are key organisms in coral reef ecosystems, where they contribute to reef building and substrate stabilization. While ocean acidification due to increasing CO2 can affect the biology, physiology and ecology of fully developed CCA, the impacts of elevated CO2 on the early life stages of CCA are much less explored. We assessed the photosynthetic activity and growth of 10 days old recruits of the reef-building crustose coralline alga Porolithon c.f. onkodes exposed to ambient and enhanced CO2 seawater concentration causing a downward shift in pH of ~0.3 units. Growth of the CCA was estimated using measurements of crust thickness and marginal expansion, while photosynthetic activity was studied with O2 microsensors. We found that elevated seawater CO2 enhanced gross photosynthesis and respiration, but significantly reduced vertical and marginal growth of the early life stages of P. c.f. onkodes. Elevated CO2 stimulated photosynthesis, particularly at high irradiance, likely due to increased availability of CO2, but this increase did not translate into increased algal growth as expected, suggesting a decoupling of these two processes under ocean acidification scenarios. This study confirms the sensitivity of early stages of CCA to elevated CO2 and identifies complexities in the physiological processes underlying the decreased growth and abundance in these important coral reef builders upon ocean acidification.